Strategic Role of Agricultural Extension Apparatus in the Development of Independent Village-Based Agricultural Business - Hamid, Hendrawati; Faisal, Muhammad; Baso, Nashar A; Jamarudddin, Jamarudddin (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study was conducted with the aim of analyzing and tracing the strategic roles implemented by Agricultural Extension officers in the development of agribusiness, which is expected to further increase village independence in building the economy through the agricultural sector, which in turn can further improve the welfare of farmers and their families. The research method used is descriptive qualitative, with respondents being agricultural extension officers, Village Heads, farmer group administrators, and female farmers, who were determined by purposive sampling and snowball sampling. Data were collected through in-depth interviews, observations, and literature studies. From the results of the study, several things were found, namely Agricultural products, especially paddy fields, are not optimal due to the unavailability of technical irrigation that is able to meet the water needs of farmers. In addition, the production produced by the community is still oriented towards household consumption. Agribusiness development needs to be directed towards market orientation and profit.